Bound by Stereotype, Freed by Independence: Represented in Larung and Cantik itu Luka: Critical Discourse Analysis - Suharyo Suharyo; Agus Nuryatin; Subyantoro Subyantoro; Mukh Doyin (Master Program in Linguistics, Diponegoro University, 2025)
Gender equality has been an issue in many societies. It becomes a highlighted issue, and novels Larung and Cantik itu Luka offer the reader insight into the issue. This research compared two novels that talk about gender issues, especially how women are represented. The research found that inequality occurs in a society because of factors of Power and Resistance from the superior and inferior groups. Using Fairclough’s Critical Discourse Analysis Framework, the researcher uncovers how the novel’s writer shares their thought about the gender issue. The analysis also integrates Halliday's Transitivity theory to parse clauses and Mills' theory of sexism to deconstruct discourse practices. The result is the gender issue that happens when there is inequality in the Proportion of chance and the dynamic role of gender in a society. This research reveals how both novels address the issue with a different approach to introduce a society that focuses on women’s perspectives of gender inequality and domination.